FRI0200 Relative effectiveness of rituximab versus an alternative TNF inhibitor in patients with rheumatoid arthritis and an inadequate response to a single previous TNF inhibitor: Results from switch-RA, a global, comparative-effectiveness, observational study. (23rd January 2014) - Emery, P.; Gottenberg, J.-E.; Sarzi-Puttini, P.; Moots, R.J.; Choquette, D.; Finckh, A.; Östör, A.; Andrianakos, A.; Barile-Fabris, L.; Desjuzeur, M.-L.; Hinsch-Gylvin, L.; Chung, C.; et al.
Abstract : Background: Recent studies indicate that RA patients (pts) with an inadequate response (IR) to a tumor necrosis factor inhibitor (TNFi) may achieve greater clinical benefit from switching to rituximab (RTX) than to an alternative TNFi. 1 SWITCH-RA, a global, multicentre, prospective, observational, clinical practice study, evaluated the relative effectiveness of RTX vs an alternative TNFi in pts with an IR to a single previous TNFi. Methods: The primary endpoint was 6-month change from baseline in DAS28 based on DAS28(3)-ESR, whichexcludes patient's global health component. Analysis of covariance adjusting for unbalanced baseline characteristics was used for treatment cohort comparisons, with missing DAS28(3)-ESR valuesimputed with investigator-reported and nearest-timepoint values. "As observed" analysis was performedto validate the results'robustness. Results: Of 1107 eligible pts (mean age 55.5 yrs; 79.0% women), 602 switched to RTX and 505 to an alternative TNFi. The RTX pts (vs alternative TNFi pts) had a mean RA disease duration of 8.9 yrs (vs 7.6, p=0.056) and a mean initial TNFi duration of 25.4 months (vs 25.2, p=0.227). At time of switch, RTX pts had greater mean baseline DAS28(3)-ESRfor the study overall (5.5 vs 5.0, p<0.001), for the sub-cohort (n=824) who discontinued initial TNFi due to inefficacy (5.3 vs 4.7, p<0.001)and for the sub-cohort (n=264) who discontinued due to intolerance (5.0 vs 4.5, p=0.019). The study had a high incidence of missing data (similar between treatment cohorts). Data for 530 (observed) and 703 (imputed) pts were available for the primary endpoint analysis. At 6 months, there were greater decreases in DAS28(3)-ESR (least squares means) in RTX than in alternative TNFi pts for overall (-1.5 vs -1.1, p=0.008) and the "inefficacy" sub-cohort (-1.5 vs -1.0, p=0.007), but not the "intolerance" sub-cohort (-1.0 vs -0.9, p=0.877). "As observed" analysis showed similar results. A greater decrease in ESR was also noted in the RTX vs the alternative TNFi group, both overall (-15.2 vs -9.2; p=0.009) and the "inefficacy" sub-cohort (-12.8 vs -6.8; p=0.035). Rates of AEs and serious AEs were similar between the treatment cohorts. Conclusions: These data from SWITCH-RA indicate that, following discontinuation of a first TNFi, pts starting treatment with RTX achieved improved effectiveness as demonstrated by significantly greater decreases in DAS28-ESR, in particular those switched for inefficacy, over 6 months compared with pts switching to an alternative TNFi. References: Finckh, et al. Ann Rheum Dis 2010;69:387. Disclosure of Interest: P. Emery Consultant for: Pfizer, Merck, Abbott, BMS, Roche, Novartis, J.-E. Gottenberg Consultant for: Abbott, BMS, Pfizer, Roche, Schering-Plough, P. Sarzi-Puttini Grant/Research support from: Roche, Pfizer, UCB, Abbott, R. Moots Grant/Research support from: Roche, UCB, MSD, D. Choquette Consultant for: Roche, Speakers Bureau: Roche, A. Finckh Grant/Research support from: Pfizer, Abbott, Roche, Consultant for: Roche, Pfizer, BMS, Speakers Bureau: Roche, A. Östör Consultant for: Roche, Chugai, Schering-Plough/MSD, Abbott, Wyeth/Pfizer, BMS, GSK, MerckSorono, UCB, A. Andrianakos Speakers Bureau: Roche, L. Barile-Fabris Consultant for: Roche, Pfizer, MSD, BMS, M.-L. Desjuzeur Employee of: F. Hoffmann-La Roche Ltd, L. Hinsch-Gylvin Employee of: F. Hoffmann-La Roche Ltd, C. Chung Employee of: Genentech, Inc, C. Mpofu Employee of: F. Hoffmann-La Roche Ltd